1988
DOI: 10.1159/000234513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drugs Used in the Treatment of Asthma on the Production of Eosinophil-Activating Factor by Monocytes

Abstract: The cytotoxic activity of eosinophils, as measured by their ability to kill antibody-coated schistosomula of Schistosoma mansoni, is enhanced by a factor (eosinophil-activating factor, EAF) which is secreted by peripheral blood monocytes from certain moderately eosinophilic individuals. The secretion of this factor by monocytes is inhibited by methylprednisolone (1 μg/ml), beclomethasone (10 μg/ml) and theophylline (100 μg/ml), but not by sodium cromoglycate or salbutamol. Methylprednisolone, beclomethasone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Our observations are consistent with the available clinical observations that a reduction of eosinophils in blood, sputum or lungs occurs in atopic asthmatic patients following treatment with cromoglycate (Diaz et al, 1984) or ketotifen (Gobel, 1978) and in patients with intrinsic bronchial asthma when treated with glucocorticosteroids (Horn et al, 1975). Furthermore, theophylline and glucocorticosteroids, but not cromoglycate or salbutamol, inhibit the production of an eosinophil-activating factor by peripheral blood monocytes obtained from individuals with moderate eosinophilia (Thorne et al, 1988). The question as to whether these drugs share a common site of action or whether they act at different points along the pathway from eosinophilpoiesis to accumulation and degranulation of eosinophils in the bronchial walls and mucus of asthmatics remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations are consistent with the available clinical observations that a reduction of eosinophils in blood, sputum or lungs occurs in atopic asthmatic patients following treatment with cromoglycate (Diaz et al, 1984) or ketotifen (Gobel, 1978) and in patients with intrinsic bronchial asthma when treated with glucocorticosteroids (Horn et al, 1975). Furthermore, theophylline and glucocorticosteroids, but not cromoglycate or salbutamol, inhibit the production of an eosinophil-activating factor by peripheral blood monocytes obtained from individuals with moderate eosinophilia (Thorne et al, 1988). The question as to whether these drugs share a common site of action or whether they act at different points along the pathway from eosinophilpoiesis to accumulation and degranulation of eosinophils in the bronchial walls and mucus of asthmatics remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…We have observed that certain of the drugs taken by these patients have an inhibitory effect in vitro on the production of EAF by mononuclear cells [ 17]. The steroid prednisolone is 50% inhibitory at 0.1 pg/ml and completely inhibitory at 1 pg/ml.…”
Section: Resultsmentioning
confidence: 89%
“…In previous work we looked at the effects of the drugs used in the treatment of the asthma patients under study on production of EAF and on activation of eosinophils by EAF [17], Of the drugs used only méthylprednisolone, at a concentra tion of 0.1 pg/ml, had a marked inhibitory effect on EAF production by blood mononuclear cells. Pa tients receiving prednisolone not only had a reduced eosinophilia but also tended to produce lower levels of EAF.…”
mentioning
confidence: 99%